Outcome during and after anticoagulant therapy in cancer patients with incidentally found pulmonary embolism. - Peris M; Jiménez D; Maestre A; Font C; Tafur AJ; Mazzolai L; Xifre B; Skride A; Dentali F; Monreal M; RIETE Investigators; Bosevski M; et al. (My University, 2016)
Current guidelines suggest treating cancer patients with incidental pulmonary embolism comparably to patients with symptomatic pulmonary embolism.We used the Registro Informatizado de Enfermedad TromboEmbólica (RIETE) registry to compare the rate of major bleeding and symptomatic pulmonary embolism during the course of anticoagulation and after its discontinuation in cancer patients with incidental pulmonary embolism.As of March 2016, 715 cancer patients with incidental pulmonary embolism had been enrolled in RIETE. During the course of anticoagulant therapy (mean 235 days), the rate of major bleeding was higher than the rate of symptomatic pulmonary embolism (10.1 (95% CI 7.48-13.4) versus 3.17 (95% CI 1.80-5.19) events per 100 patient-years, respectively), and the rate of fatal bleeding was higher than the rate of fatal pulmonary embolism (2.66 (95% CI 1.44-4.52) versus 0.66 (95% CI 0.17-1.81) deaths per 100 patient-years, respectively). After discontinuing anticoagulation (mean follow-up 117 days), the rate of major bleeding was lower than the rate of symptomatic pulmonary embolism (3.00 (95% CI 1.10-6.65) versus 8.37 (95% CI 4.76-13.7) events per 100 patient-years, respectively); however, there were no differences in the rate of fatal events at one death each.The risk/benefit ratio of anticoagulant therapy in cancer patients with incidental pulmonary embolism is uncertain and must be evaluated in further studies.